Pinellia ternata attenuates carotid artery intimal hyperplasia and increases endothelial progenitor cell activity via the PI3K/Akt signalling pathway in wire-injured rats - Hai-Ke Lu; Yan Huang; Xiao-Yu Liang; Ying-Yi Dai; Xin-Tong Liu (Taylor & Francis Group, 2020)
Context Clinically, Pinellia ternata (Thunb.) Breit. (Araceae) (PT) has been widely used in the treatment of atherosclerosis and hyperlipidaemia, but the underlying mechanisms are still not clearly understood. Objective This research was conducted to confirm the mechanism by which PT affects carotid artery intimal hyperplasia. Materials and methods An intestinal hyperplasia Sprague-Dawley rat model was established by carotid artery injury. The rats were randomly divided into five groups (n = 8): sham, model, PT (with daily intragastric administration of 10 g/mL/kg PT tubers water extract), PT+LY294002 (with intraperitoneal injection of 50 mg/kg LY294002 + 10 g/mL/kg PT) and endothelial progenitor cells (EPCs) (with injection of 5 × 105/cells), and treated for 4 or 8 weeks. Results HE staining showed that PT attenuated intimal hyperplasia. RT-PCR, Western blotting and immunohistochemistry showed that PT increased the expression of vascular endothelial growth factor (VEGF) and eNOS in the atherosclerotic carotid artery. PT increased the Dil-acLDL+/FITC-UEA-1+ population (from 0.41 ± 0.085% to 0.60 ± 0.092%) in the blood, decreased TCHO, TG, LDL-C, IL-6 and TNF-α levels, and increased HDL-C and IL-10 levels in the blood. However, these changes were reversed by the PI3K/Akt pathway inhibitor LY294002. Discussion and conclusions PT can be developed as an atherosclerosis and carotid intimal hyperplasia treatment drug. Therefore, further study will focus on the effects of PT on intimal hyperplasia in wire-injured atherosclerosis patients and explore in depth some other relevant molecular mechanisms.